2021
DOI: 10.1016/j.marpolbul.2021.112739
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 restrictions and their influences on ambient air, surface water and plastic waste in a coastal megacity, Chennai, India

Abstract: Anthropogenic activities experienced a pause due to the nationwide lockdown, imposed to contain the rapid spread of COVID-19 in the third week of March 2020. The impacts of suspension of industrial activities, vehicular transport and other businesses for three months (25 March-30 June) on the environmental settings of Chennai, a coastal megacity was assessed. A significant reduction in the key urban air pollutants [PM 2.5 (66.5%), PM 10 (39.5%), NO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The effect of anthropogenic activities that cause environmental degradation has been diminished due to the pause of these activities in the face of measures to contain the rapid spread of COVID-19 [70]. The impacts of the suspension of industrial activities, vehicular transport and other businesses should be part of the new challenges to be measured, as policy makers and stakeholders must also assess which blue products could also be affected by these types of stoppages and which would cause a delay in the progress of policies associated with blue growth [18].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of anthropogenic activities that cause environmental degradation has been diminished due to the pause of these activities in the face of measures to contain the rapid spread of COVID-19 [70]. The impacts of the suspension of industrial activities, vehicular transport and other businesses should be part of the new challenges to be measured, as policy makers and stakeholders must also assess which blue products could also be affected by these types of stoppages and which would cause a delay in the progress of policies associated with blue growth [18].…”
Section: Discussionmentioning
confidence: 99%
“…Robin et al analyzed the types and amounts of plastics contained in biomedical wastes in India, and found an increase of 17% due to the COVID-19 pandemic in 2021. FTIR-ATR analysis revealed 25.4% PP and 15.4% polyester in the studied types of PPE [ 261 ]. The authors identified 14 polymer types in the evaluated PPE samples.…”
Section: Multiresistant Infection Prevention Including the Covid-19 P...mentioning
confidence: 99%
“… Composition of polymers in the selected commercially available PPE [ 261 ]. Reproduced with permission from Elsevier.…”
Section: Figurementioning
confidence: 99%
“…In recent past, many papers have been published worldwide showing overall improvement of water quality due to COVID-19-related lockdown and cessation of anthropogenic activities (Chakraborty et al 2021). Robin et al (2021) reported fewer plastic waste in the coastal water due to reduced anthropogenic activity in the Chennai coast. According to Yunus et al (2020), the quality of lake water in China has improved as a result of COVID-19-related lockdown.…”
Section: Global Scenario Of the Improved Water Quality Due To The Loc...mentioning
confidence: 99%